Effects of Sintering Temperature and Yttria Content on Microstructure, Phase Balance, Fracture Surface Morphology, and Strength of Yttria-Stabilized Zirconia - Volodymyr Kulyk; Zoia Duriagina; Andrii Kostryzhev; Bogdan Vasyliv; Olexandra Marenych (Applied Sciences, 2022)
Currently, ceramics are widely used in various industry branches, especially in energy, chemistry, and aerospace, as well as in medicine. Yttria-stabilized zirconia (YSZ) having unique electrical, thermal, and mechanical properties is one of the most popular ceramics for such applications. In this study, the influence of sintering temperature and yttria percentage on the microstructure and mechanical behavior of YSZ ceramics have been investigated. Corresponding mixtures of ZrO2 powder doped with 3 and 6 mol% Y2O3 powders (hereinafter: 3YSZ and 6YSZ) were prepared, and a series of ceramic specimens were sintered in argon at 1450 °C, 1500 °C, and 1550 °C for 2 h. Changes in the morphology and size of microstructural components as well as their distribution were analyzed with respect to the sintering mode, phase composition, flexural strength, and fracture surface morphology. The 3YSZ and 6YSZ ceramics sintered for 2 h at 1550 °C and 1450 °C, respectively, exhibited the highest levels of strength due to the presence of agglomerates of fine tetragonal zirconia phase particles with high bond strength, as well as larger grains of the monoclinic zirconia phase. The dominant fracture micromechanisms in both the 3YSZ and 6YSZ ceramics related to their high strength are discussed.